(untitled) (Research, Society and Development, 2020)
Considering the several methods proposed with the objective of estimating the stress increase in unbonded tendons of prestressed concrete structural elements, not existing therefore one single guideline for this purpose, it is observed the need for a more comprehensive investigation on the subject. This work focuses on the simplified method for estimating the stress variation in unbonded tendons in accordance with NBR 6118 (ABNT, 2014). With the methodology proposed by the code, reliability analyzes are carried out, using the analytical methods FORM and Monte Carlo, of beam requested by its average value of flexural strength, constituted by live and permanent loads. The analysis considered different values of the compressive strength of the concrete and a variation of percentage of the live load acting on the analyzed beam. A sensitivity study is also conducted that highlights the greater relevance among random variables considered. The values of the reliability indices highlight the conservative values of the stress increase in unbonded tendons obtained from the proposal indicated by NBR 6118 (ABNT, 2014).